A Homozygous KCNJ10 Mutation in Jack Russell Terriers and Related Breeds with Spinocerebellar Ataxia with Myokymia, Seizures, or Both. (7th April 2014) - Gilliam, D.; O'Brien, D.P.; Coates, J.R.; Johnson, G.S.; Johnson, G.C.; Mhlanga‐Mutangadura, T.; Hansen, L.; Taylor, J.F.; Schnabel, R.D.
<x xml:space="preserve">Abstract</x> Background Juvenile‐onset spinocerebellar ataxia has been recognized in Jack Russell Terriers and related Russell group terriers (RGTs) for over 40 years. Ataxia occurs with varying combinations of myokymia, seizures, and other signs of neurologic disease. More than 1 form of the disease has been suspected. Hypothesis/Objectives The objective was to identify the mutation causing the spinocerebellar ataxia associated with myokymia, seizures, or both and distinguish the phenotype from other ataxias in the RGTs. Animals DNA samples from 16 RGTs with spinocerebellar ataxia beginning from 2 to 12 months of age, 640 control RGTs, and 383 dogs from 144 other breeds along with the medical records of affected dogs were studied. Methods This case‐control study compared the frequencies of a KCNJ10 allele in RGTs with spinocerebellar ataxia versus control RGTs. This allele was identified in a whole‐genome sequence of a single RGT with spinocerebellar ataxia and myokymia by comparison to whole‐genome sequences from 81 other canids that were normal or had other diseases. Results A missense mutation in the gene coding for the inwardly rectifying potassium channel Kir4.1 (KCNJ10:c.627C>G) was significantly (P < .001) associated with the disease. Dogs homozygous for the mutant allele all had spinocerebellar ataxia with varying combinations of myokymia and seizures. Conclusions and Clinical Importance Identification of the KCNJ10 mutation in dogs with spinocerebellar ataxia with myokymia, seizures, or both clarifies the multiple forms of ataxia seen in these breeds and provides a DNA test to identify carriers.